Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai - Agung Hartadi (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine whether there is an influence of leadership style and work environment on the performance of pharmacy installation staff at TK III Hospital 04.06.03 dr. Soetarto Yogyakarta. This study uses the independent variables of leadership style and work environment while the dependent variable uses employee performance. This study used a quantitative method, the population of this study were employees of the pharmaceutical installation. Samples were taken by census method. Distribution of questionnaires as many as 30 respondents. This method uses IBM SPSS Statistics 22 multiple linear regression analysis, with the t test and F test. The results of this study indicate that there is no influence of leadership style with a significant value of 0.313 on the performance of pharmacy installation employees and there is an effect of the work environment on the performance of pharmaceutical installation employees with a value significant 0.004. Simultaneously, there is the influence of leadership style and work environment on the performance of pharmacy installation employees at TK III Hospital 04.06.03 dr. Soetarto Yogyakarta with a significant value of 0.10 whose contribution to variations or fluctuations in performance is 28.8% and the remaining 71.2% is influenced by other variables.